Analysis of Approaches to the Assessment of Innovative Development of Economic System in the Region - P. S. Vagina; A. V. Kravchenko; Yu. N. Lyachenkov (Управленческое консультирование)
In the article the structure of regional innovative system is investigated and its conceptual model opening an essence of innovative activity is developed. The system of the indicators allowing to estimate the level of innovative development of regional economies is offered and the directions regarding improvement of the operating assessment techniques are designated. The author’s structure of the index of innovative development of regions consisting of four subindexes reflecting a condition of regional innovative system is offered; it is shown that assessment of regional economic systems with use of author’s approach allows to keep track of dynamics of development of regional innovative systems for development of organizational and administrative decisions on increase in their efficiency.